The effects of rewards on executive function in preschoolers. - Lim, Huiqing. (2010)
The key findings of this study showed that rewards can facilitate performance in an executive function (EF) task when reward is contingent on performance. Rewards enhanced children’s information updating skills when children were either told they would be rewarded with a prize of considerable salience for their performance on a task, or were told nothing about receiving a reward. Preschoolers aged between 4 and 5 years (N = 46) engaged in a working memory task. The study was a between-subjects design with 2 levels of condition (Reward-informed and Reward-uninformed). An increase in attribution of reward to one’s own competence was proposed as a possible explanation for the effect of reward on children’s high performance in the executive function task.